2013
DOI: 10.3892/ijo.2013.2132
|View full text |Cite
|
Sign up to set email alerts
|

Increased killing of SCCVII squamous cell carcinoma cells after the combination of Pc 4 photodynamic therapy and dasatinib is associated with enhanced caspase-3 activity and ceramide synthase 1 upregulation

Abstract: Photodynamic therapy (PDT) is not always effective as an anticancer treatment, therefore, PDT is combined with other anticancer agents for improved efficacy. The combination of dasatinib and PDT with the silicone phthalocyanine photosensitizer Pc 4 was assessed for increased killing of SCCVII mouse squamous cell carcinoma cells, a preclinical model of head and neck squamous cell carcinoma, using apoptotic markers and colony formation as experimental end-points. Because each of these treatments regulates the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…). This finding of the interaction of a sphingolipid metabolism‐modulating drug and PDT at the cellular level is consistent with previously published in vitro studies documenting the enhancement of PDT‐mediated cell killing by short‐chain cationic ceramide LCL29, or drugs modifying the activity of ceramide‐generating enzymes such as dasatinib and fenretinide …”
Section: Discussionsupporting
confidence: 91%
“…). This finding of the interaction of a sphingolipid metabolism‐modulating drug and PDT at the cellular level is consistent with previously published in vitro studies documenting the enhancement of PDT‐mediated cell killing by short‐chain cationic ceramide LCL29, or drugs modifying the activity of ceramide‐generating enzymes such as dasatinib and fenretinide …”
Section: Discussionsupporting
confidence: 91%
“…SCC17B cells were chosen for the study as a clinically-relevant HNSCC model because the cells were derived from a non-metastatic cancer of the larynx, a PDT-treatable HNSCC type [18]. We used Pc4 as the photosensitizer, because our in vitro data showed that combining Pc4PDT with dasatinib, a clinically-approved anticancer agent, enhances cell killing [19]. Also Pc4PDT has been shown to be a promising anticancer treatment in human patients [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis was placed on the enzymes regulating the metabolism of two sphingolipids with opposing functions, namely pro‐apoptotic ceramide and pro‐proliferative sphingosine 1‐phosphate. In several previous investigations, ceramide was shown to be de novo synthesised and accumulate in response to PDT, and in a recent study by Separovic et al., PDT decreased sphingosine levels and inhibited the activity of acid ceramidase (ASAH) …”
Section: Resultsmentioning
confidence: 95%
“…In severalp reviousi nvestigations,c eramide was shownt ob ed enovo synthesised and accumulate in response to PDT, [37] and in ar ecent study by Separovic et al,P DT decreasedsphingosine levels and inhibited the activity of acidceramidase(ASAH). [40] The tested compounds upon irradiationo fH CT116 cells did not induce significant changes in the expression levels of ASAH,c eramide synthase 6( LASS6) and phospho-sphingosine kinase 1( SphK1;F igure 10). This finding suggests that these enzymes do not mediate the antitumour effects of the tested compounds in HCT116 cells.…”
Section: Inhibitory Effectsone Nzymes Regulating Ceramide and Sphingomentioning
confidence: 93%
See 1 more Smart Citation